2015
DOI: 10.3899/jrheum.150270
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for a Candidate Core Set of Fitness and Strength Tests for Patients with Childhood or Adult Idiopathic Inflammatory Myopathies

Abstract: OBJECTIVES Currently there are no evidence-based recommendations regarding which fitness and strength tests to use for patients with childhood or adult idiopathic inflammatory myopathies (IIM). This hinders clinicians and researchers in choosing the appropriate fitness- or muscle strength-related outcome measures for these patients. Through a Delphi survey, we aimed to identify a candidate core-set of fitness and strength tests for children and adults with IIM. METHODS Fifteen experts participated in a Delph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Our findings seem to substantiate this recommendation, as some of the muscle strength/function tests applied in this study (i.e., 1-RM bench press, 1-RM leg press, timed-stands test) revealed lower muscle function in JDM patients, all of them with maximal scores in MMT. Therefore, we reinforce the idea that a series of tests, rather than only MMT and/or handgrip, should be applied in either clinical setting or research to sensitively assess muscle function in chronic JDM patients, with the guidance of the recently proposed core set [37]. Previous studies have shown that JDM patients often experience decreased strength and aerobic and anaerobic capacity [4][5][6].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Our findings seem to substantiate this recommendation, as some of the muscle strength/function tests applied in this study (i.e., 1-RM bench press, 1-RM leg press, timed-stands test) revealed lower muscle function in JDM patients, all of them with maximal scores in MMT. Therefore, we reinforce the idea that a series of tests, rather than only MMT and/or handgrip, should be applied in either clinical setting or research to sensitively assess muscle function in chronic JDM patients, with the guidance of the recently proposed core set [37]. Previous studies have shown that JDM patients often experience decreased strength and aerobic and anaerobic capacity [4][5][6].…”
Section: Discussionsupporting
confidence: 54%
“…Another possible insight from the current study is that conventional clinical measures may be not sufficiently sensitive to detect impairments in fitness and functionality in chronic JDM patients with mild disease and no clinical evidence of muscle dysfunction. Recently, a candidate core set of fitness and strength tests for JDM patients was proposed through a Delphi survey [37]. This core set recommends the use of MMT to assess muscle strength; however, in order to improve the knowledge on the patient's strength, additional tests are advised when MMT score of Z6 is achieved in a particular muscle group.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been a proposal for a candidate coreset of fitness and strength tests for patients with childhood or adult IIMs. It includes treadmill exercise stress test (modified Bruce protocol), incremental cycle ergometer test, 6 min walk test (6MWT), handgrip strength, MMT, CMAS in children, and FI-2 in adults [152] .…”
Section: Treatment In Dmmentioning
confidence: 99%
“…Based on a Delphi exercise, handgrip strength assessment with dynamometer and manual muscle testing (MMT8) were recently included in the core set of muscle strength tests for patients with idiopathic inflammatory myopathy (130). Performance-based functional capacity testing was also recommended in patients with inflammatory myopathy for a better characterisation of the disease.…”
Section: Muscle Involvementmentioning
confidence: 99%